The Impact of EFL Students' Speaking Anxiety on Learning Achievement: Dampak Kecemasan Berbicara Siswa EFL Pada Prestasi Belajar - Dwi Kalsum Pertiwi (Jurnal Kreatif Online, 2021)
Abstract This research investigates the speaking anxiety faced by the third-year undergraduate students at English Education Study Program of Tadulako University. The methodology that is used in this research is mixed method. The sample is selected by using purposive sampling technique for research participants consisting of 38 students. Data are collected through questionnaire, semi-structured interview, and documentation. In this research, the researcher find that the factor that mostly causes the students speaking anxiety is the students’ lack of preparation. The strategy that mostly used by the students to reduce their anxiety are preparation and practicing. Most of the students’ level of anxiety is “Anxious”. 6 students (15.7%) experience "Very Anxious" level, 20 students (52.6%) experience “Anxious” level, 11 students (28.9%) experienced "Mildly Anxious" level, 1 student (2.6%) experience "relaxed" level, and no student (0%) experience "very relaxed" level. Most of the students still get high speaking score regardless of their high level of speaking anxiety, it shows how good the students handling their speaking anxiety by using their strategies so that they can manage to speak and perform well in class. The researcher concludes that the strategies used by the students had a positive impact in improving their learning achievement. Key Words: Speaking, Speaking Anxiety.